PERLINDUNGAN KONSUMEN ATAS KEBOCORAN DATA PRIBADI PADA PENGGUNA APLIKASI AKULAKU BERDASARKAN PERATURAN OTORITAS JASA KEUANGAN NOMOR 1/POJK.07/2013 TENTANG PERLINDUNGAN KONSUMEN SEKTOR JASA KEUANGAN - Adriani Elisabet Cahyaninglintang Sinaga; Jeane Neltje Tampi (Fakultas Hukum Universitas Tarumanagara, 2021)
Fintech or P2P Lending is a service that is engaged in financial services where it has consumers. Consumers who use their own financial services in Indonesia have been protected by several regulations, one of which is Peraturan Otoritas Jasa Keuangan Number 1/POJK.07/2013 concerning Consumer Protection in the Financial Services Sector which aims to create protection for you, increase consumer empowerment, and raise awareness. Financial Services Businesses regarding the importance of Consumer Protection. However, consumers who use Akulaku's Financial services are in a position where their personal data is leaked. In this case, the consumer's personal data leak resulted in Kredit Tanpa Agunan (KTA) bills and purchase transactions that were never entered into the Consumer's Akulaku account. Until now, consumers have not received a solution to the leakage of personal data they experienced.